Community engagement: mentor beliefs across training and experience. Issue 1 (1st January 2020) - Matheson, David W.; Rempe, Gary; Saltis, Michelle N.; Nowag, Amanda D.
ABSTRACT: The purpose of this quantitative study was to understand how training and the development of the mentoring relationship impacts mentor beliefs across time within a therapeutic mentoring program called Campus Connections, a community engagement program that pairs university undergraduate and graduate students with youth from the local community in a mentoring relationship for an academic semester. Specifically, we studied how mentor beliefs are constructed at the start of the mentoring program, how these beliefs shift after four weeks of training, and how mentor beliefs change after participating in the mentoring process during an academic semester. Results indicated mentors held unhelpful mentoring beliefs prior to training and that training combined with the mentoring relationship created a positive impact on mentoring beliefs. Implications for the mentoring relationship and community engagement programs are discussed based on the trajectory of mentor beliefs within the study.